Solidarność Dolnośląska . tygodnik NSZZ "Solidarność", no. 42, 1981 - [ed. Stanisław Huskowski, Krzysztof Turkowski, Maciej Zięba] (Zarząd Regionalny NSZZ "Solidarność" we Wrocławiu, 1981)
Print run: 10000 copies